Development of Visual, Auditory, Kinesthetic (VAK) Based Student Worksheets Assisted by Liveworksheets - Ellianawati Ellianawati; Murni Murni; Bambang Subali; Suharto Linuwih; Nguyen Van Bien (FKIP Universitas Lampung, 2024)
Development of Visual, Auditory, Kinesthetic (VAK) Based Student Worksheets Assisted by Liveworksheets. Objectives: This study aims to develop Visual, Auditory, Kinesthetic (VAK)-based student worksheets assisted by liveworksheets that are feasible, practical and effective to improve students' cognitive learning outcomes and science literacy abilities. Methods: This study is a type of research and development (R&D) with data collection techniques in the form of feasibility test questionnaires, practicality test questionnaires, and effectiveness test instruments designed in accordance with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The sample used to test the effectiveness of the student workshets was 32 students of class X SMA Negeri 12 Semarang with a one group pre test-post test design. The data analysis technique used in this study is Aiken's formula to analyze the feasibility of student worksheets, the percentage of practicality to analyze the practicality of student worksheets, and the n-gain equation to analyze the effectiveness of student worksheets. Findings: The development of Visual, Auditory, Kinesthetic (VAK) based student worksheets assisted by liveworksheets based on the feasibility test obtained a score of 0.92 with the category “feasible”. Based on the practicality test obtained a score of 92% with the category “very practical”. Based on the effectiveness test, the n-gain score was 0.64 for cognitive learning outcomes in the “medium” category and 0.74 for science literacy abilities in the “high” category. Conclusion: Visual, Auditory, Kinesthetic (VAK)-based student worksheets assisted by liveworksheets are feasible, practical and effective to improve students' cognitive learning outcomes and science literacy abilities. Keywords: student worksheets, VAK learning model, liveworksheets.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202455